Effect of Laser on Phagocytic Activity of Polymorphoneutrophils - Khaleel, Aida Z.; Al-Ghurabi, Batool H.; Al-Saady, Luma G. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: It is well known that the low level laser irradiation has act on immune system cells in a number of ways, one of them includes increasing phagocytic activity of irradiated cells. This study was established to shed light on the possible effect of laser irradiation on phagocytic activity of polymorphoneutrophils.Subjects and methods: Fresh blood samples were obtained from twenty healthy volunteers for phagocytosis assay. The polymorphoneutrophils were isolated from blood and examined their phagocytic capacity befor and after exposure to laser irradiation.Results: The present study revealed a significant increase in the mean percentage of phagocytosis after exposure to diode laser of wave length (632) nm (red), which was further increased by increasing the time of exposure.Conclusion: The current study suggests that low level of laser can increase the phagocytic activity of polymorphoneutrophils, and this increase propotional to increaseing the time of exposure.